1988
DOI: 10.1007/bf00397659
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterisation of monoclonal and polyclonal antibodies to maize membrane auxin-binding protein

Abstract: Binding proteins, thought to be auxin receptors, can be solubilised from maize (Zea mays L.) membranes after acetone treatment. From these crude extracts, receptor preparations of over 50% purity can be obtained by a reliable, straight-forward procedure involving three chromatographic steps - anion exchange, gel filtration and high-resolution anion exchange. Such preparations have been used to immunise rats for subsequent production of monoclonal antibodies. By the further step of native polyacrylamide gel ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 20 publications
4
79
0
Order By: Relevance
“…The polyclonal antibody against ABP1, but not the preimmune antiserum, immunoprecipitates a 22-kD protein photolabeled with [3H]5-N3IAA. The recognition of the 22-kD band by these antibodies comigrated with recognition by antibodies previously described by Napier et al (23). Furthermore, antisera used by Napier et al (23) The level of IAA and IAA esters in the apical mesocotyl was determined by GC-SIM-MS using '3C6-IAA as an internal standard as described by Chen et al (7), and it was found that 2 h after continuous irradiation the free IAA level was approximately 50% of the dark control tissue (Fig.…”
Section: Materials and Methods Plant Tissue Chemicals And Light Treamentioning
confidence: 72%
See 1 more Smart Citation
“…The polyclonal antibody against ABP1, but not the preimmune antiserum, immunoprecipitates a 22-kD protein photolabeled with [3H]5-N3IAA. The recognition of the 22-kD band by these antibodies comigrated with recognition by antibodies previously described by Napier et al (23). Furthermore, antisera used by Napier et al (23) The level of IAA and IAA esters in the apical mesocotyl was determined by GC-SIM-MS using '3C6-IAA as an internal standard as described by Chen et al (7), and it was found that 2 h after continuous irradiation the free IAA level was approximately 50% of the dark control tissue (Fig.…”
Section: Materials and Methods Plant Tissue Chemicals And Light Treamentioning
confidence: 72%
“…We have reexamined this problem by looking at the kinetics of the R-induced changes in IAA level, ABP1 level (18,23), and growth kinetics. Because there is some indirect evidence that ABP1 may mediate auxin effects on cell walls (e.g.…”
mentioning
confidence: 99%
“…Control experiments with antibodies against a luminal epitope, i.e. the KDEL endoplasmic reticulum retention signal (30,31), showed that digitonin did not permeabilize the endoplasmic reticulum membrane. For the major hydrophilic loop domain, essentially identical results were obtained.…”
Section: Discussionmentioning
confidence: 98%
“…To analyze this question, we used low concentrations of digitonin to selectively permeabilize the plasma membrane (see "Materials and Methods") and antibodies against the amino-terminal domain (antiserum B14), against the Myc tag introduced at the amino terminus (mAb 9E10), against the second loop domain (antibody 519), and, finally, against the hydrophilic loop domain (antiserum B16) of PS1. To monitor the permeabilization procedure, rat monoclonal antibody against the luminal endoplasmic reticulum retention signal KDEL was used (30,31). Antibodies against the amino-terminal domain of PS1, against the amino-terminally inserted Myc tag (Fig.…”
Section: Cytoplasmic Orientation Of the Amino-terminal Domain And Hydmentioning
confidence: 99%
“…LAMP and CD63 antibodies were obtained from the Developmental Studies Hybridoma Bank, University of Iowa (LAMP-1 clone H4A3, LAMP-2 clone H4B4, CD63 clone H5C6), anti-LBPA was a gift from J Gruenberg (Department of Biochemistry, University of Geneva, Switzerland), 35 anti-KDEL MAC256 was a gift from G Butcher (The Babraham Institute, Babraham, UK) 36 and anti-EEA1 and anti-Golgi GM130 were from BD Biosciences (Pharmingen). Secondary antibodies were from Jackson Immunoresearch Labs.…”
Section: Methodsmentioning
confidence: 99%